PENETAPAN DISPENSASI KAWIN KARENA FAKTOR HAMIL DAN AKBAT HUKUMNYA DITINJAU DARI HUKUM ISLAM DAN HUKUM POSITIF (Studi di Pengadilan Agama Bengkulu) - Noviantoro, Wawan (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2019)
The marriage dispensation is filed by the parents of the man and woman to the Religious Court which is his residence, the Religious Court after examining in court and believes that there are possible matters to grant the dispensation, the Religious Court provides the marriage dispensation with a determination. The Panel of Judges provides the stipulation under article 7 paragraph (1) of Law Number 1 Year 1974, with the consideration to avoid the occurrence of greater mudharat such as pregnancy before marriage.The child marriage under age due to pregnant factors base on Islamic law concerning with themarital status and the status of children born after six months of marriage have nasab, guardianship, inheritance and livelihoods of both parents. However, if the child is born before six months of marriage, it has no nasab, guardianship, inheritance and livelihood relationships from his father, unless there is recognition and proof of the child's biological relationship.